Household Food Insecurity, Low Dietary Diversity, and Early Marriage Were Predictors for Undernutrition among Pregnant Women Residing in Gambella, Ethiopia - Mamo Nigatu; Tsegaye Tewelde Gebrehiwot; Desta Hiko Gemeda (Advances in Public Health)
Background. Maternal undernutrition affects the health of both mothers and children and, as a result, has broad impacts on economic and social development. Objective. The aim of this study was to assess magnitude of undernutrition and associated factors among pregnant women in Gambella town, 2014. Methods. Community based cross-sectional study was conducted on 338 randomly selected pregnant women from March to April 2014. Bivariate and multivariable logistic regressions were used for data analysis. Result. The prevalence of undernutrition among pregnant women in Gambella town was 28.6%. Pregnant women who were married before their age of eighteen, who were from food insecure households, and who had low dietary diversity score were nearly four (AOR = 3.9, 95% CI: 2.2–6.9), two (AOR = 2.3, 95% CI : 1.2–3.6), and two (AOR = 2.1, 95% CI: 1.3–4.16) times more likely to be undernourished as compared to their counterparts, respectively. Conclusion. Prevalence of undernutrition among pregnant women in Gambella town was unacceptably high. Stake holders should give due consideration to health education to delay age at first marriage and mainstreaming and strengthening nutritional activities that contribute to reduction of food insecurity and consumption of unbalanced nutrients.